Exploration of Oryza sativa drought-responsive element binding protein 2A (OsDREB2A) gene in several local Indonesian rice varieties - YULIZA YULIZA; ANDI SALAMAH; HARDINI PUSPITANINGRUM (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Yuliza, Salamah A, Puspitaningrum H. 2024. Exploration of Oryza sativa drought-responsive element binding protein 2A (OsDREB2A) gene in several local Indonesian rice varieties. Biodiversitas 25: 574-582. Drought is one of the abiotic stress factors that reduces rice productivity in Indonesia. OsDREB2A is a member of the DREBP subfamily of AP2/ERF transcription factors and participates in drought stress by directly binding to DRE elements to regulate downstream gene expression. However, further research is still needed to observe each OsDREB2A gene in local Indonesian rice varieties. This research aims to explore the OsDREB2A gene in several local Indonesian rice varieties, namely from Java (Ciherang, Situbagendid, Way Apo, Inpara 32 and Inpari 42), Kalimantan (Black Rice),  Aceh (Sigupai) and West Sumba (Pare Lambem and Pare Bakato Kaka). DNA was isolated from the leaves of each variety, amplified using PCR, and then electrophoresed and sequenced. Sequencing data were analyzed using DNA Baser, BioEdit and then visualized using the SWISS-MODEL server, Rice Genome Annotation Project Database, and chromosome map tools. The results showed that nine samples had 100% query cover with the Pokkali OsDREB2A (KU159743.1) cultivar sequence, 99.86% similar percent identity compared to cultivar R180 and WAB540-1-B-P-6-1-1, 99.75% similar percent identity compared to cultivar FL-478 and 99.62% similar percent identity compared to cultivar Nona Bokra. The amino acid structure of each cultivar refers to chromosome 1 at the LOC_Os01g07120 locus.